Morphology and phylogeny reveal two novel Xylaria (Xylariaceae) species from China - Wu, You-Peng; Pi, Yin-Hui; Long, Si-Han; Liu, Li-Li; Zhang, Xu; Long, Qing-De; Lin, Yan; Kang, Ying-Qian; Kang, Ji-Chuan; Wijayawardene, Nalin N.; Li, Qi-Rui (Phytotaxa, 2022)
Four species of Xylaria were collected from Guizhou and Hainan provinces in China. Morphological and phylogenetic analyses (based on β-tubulin, rpb2 and α-actin genes) revealed two new species (X. sylvatica sp. nov. and X. wuzhishanensis sp. nov.) and two known species (X. atrosphaerica and X. cubensis). Xylaria sylvatica is distinguished from X. spinulosa by lacking long thorns on the stromatal surface, and larger ascospores (23–28.5 × 7–9.5 μm vs. 19–23 × 6.5–8.5 μm) with a sigmoid germ slit. Xylaria wuzhishanensis differs from X. schweinitzii by its semi-globular or irregularly globose stromata, from X. atrosphaerica by its larger ascospores (23–30.5 × 7–9 μm vs. 17–25 × 6–10 μm). Their descriptions and illustrations are provided.